MO286DESIGN OF A PH1, MULTICENTER TRIAL TO INVESTIGATE THE SAFETY, TOLERABILITY, PK/PD OF BION-1301 IN HEALTHY VOLUNTEERS AND ADULTS WITH IGAN AND A MULTICENTER, OPEN-LABEL EXTENSION STUDY FOR IGAN PATIENTS WHO PARTICIPATED IN A PRIOR TRIAL OF BION-1301. (29th May 2021) - Barratt, Jonathan; Mittan, Angelique; Roy, Suzanne; Sibley, Cailin; Stromatt, Colleen; Endsley, Aaron; Lo, Jeannette; Glicklich, Alan
Abstract: Background and Aims: IgA nephropathy (IgAN), the leading cause of primary glomerulonephritis, is an autoimmune disease with no approved treatments. 1 Progression to end-stage-renal disease occurs in up to 45% of IgAN patients, requiring dialysis or kidney transplant to manage. 2-4 A critical step in IgAN pathogenesis is the production of galactose-deficient IgA1 (Gd-IgA1) leading to the generation of anti-Gd-IgA autoantibodies and the formation of immune complexes that result in kidney inflammation and damage. 5 A Proliferation-Inducing Ligand (APRIL), a soluble factor that regulates B cell differentiation, proliferation and survival of plasma cells, and IgA class-switching is elevated in patients with IgAN 6, 7 . IgAN patients with high plasma APRIL levels are reported as having higher levels of Gd-IgA1 and proteinuria and lower estimated glomerular filtration rates compared to those with lower plasma APRIL levels. 7 BION-1301 is a novel humanized blocking antibody targeting APRIL. The primary objective of Study ADU-CL-19 is to assess the short-term safety and tolerability of BION-1301 in Healthy Volunteers (HV) and IgAN patients and to secondarily assess the short-term pharmacokinetics (PK), pharmacodynamics (PD), immunogenicity, and preliminary clinical activity of BION-1301. The primary objective of Study ADU-CL-24 is to characterize the long-term safety of BION-1301 in IgAN patients who completed treatment in ADU-CL-19 while secondarily assessing the long-term PK, PD, immunogenicity, and preliminary clinical activity of BION-1301. Method: The Phase 1 study (ADU-CL-19; NCT03945318) comprises 3 parts. Parts 1 and 2 are double-blind, randomized, placebo-controlled single and multiple ascending dose designs in HV; both parts have been completed. Part 3 is an ongoing multicenter (US and UK), multiple-dose, two cohort design in approximately 20 patients with IgAN (10/cohort). Key eligibility criteria for Part 3 includes: (1) urine protein ≥0.5 g/24h or baseline UPCR ≥0.5 g/g, (2) stable/optimized dose of ACE-I/ARB or intolerant to ACE-I/ARB, and (3) biopsy-verified diagnosis of IgAN within the past 10 years. In Part 3, patients in Cohort 1 are receiving BION-1301 at 450mg every 2 weeks for 3 months. The dose and schedule for Cohort 2 will be determined by the Safety Review Team (SRT) based on data from the first 5 patients. After 3 months of treatment, patients continue safety follow-up for approximately 6 months unless deciding to enroll in the open-label extension (OLE) study, withdraw from the study, or are lost to follow up. Study ADU-CL-24 (NCT04684745) is a Phase 2 Open-Label Extension (OLE) of Study ADU-CL-19. Eligibility for the OLE study is restricted to those patients who completed at least 75% of their intended doses as well as the End of Treatment (EOT) visit in Study ADU-CL-19. Patients who enroll directly from the ADU-CL-19 EOT visit are not required to attend an additional screening visit. This is encouraged to maintain un-interrupted dosing. Once enrolled in the OLE, patients receive BION-1301 at the same dose and regimen as assigned in the parent study for up to 2 years. The dose, route, and regimen of BION-1301 may change after review of emergent safety, PK, PD and efficacy data by the SRT. Results: Parts 1 and 2 of the Phase 1 study in HV are complete and the data were presented at ASN in 2020 8 Part 3 of the Phase 1 and the Phase 2 OLE study are ongoing, and interim results from the first dose cohort in IgAN patients are being presented in a separate poster at this meeting. Conclusion: The design of the Phase 1 and Phase 2 OLE studies described in HVs and IgAN patients have enabled the generation of short- and long-term safety, PK, PD, immunogenicity and preliminary efficacy data for BION-1301. The Phase 1 short-term data will guide the design of future later-stage trials of BION-1301, while the long-term data from OLE will enable a greater understanding of the potential long-term risk/benefit profile of BION-1301 in IgAN patients.